Costs of two vancomycin-resistant enterococci outbreaks in an academic hospital - Simon van der Pol; Mariëtte Lokate; Maarten J. Postma; Alex W. Friedrich (Cambridge University Press, 2023)
Abstract Objective: In early 2017, the University Medical Center Groningen, the Netherlands, had an outbreak of 2 strains of vancomycin-resistant enterococci (VRE) that spread to various wards. In the summer of 2018, the hospital was again hit by a VRE outbreak, which was detected and controlled early. However, during both outbreaks, fewer patients were admitted to the hospital and various costs were incurred. We quantified the costs of the 2017 and 2018 VRE outbreaks. Design: Using data from various sources in the hospital and interviews, we identified and quantified the costs of the 2 outbreaks, resulting from tests, closed beds (opportunity costs), cleaning, additional personnel, and patient isolation. Setting: The University Medical Center Groningen, an academic hospital in the Netherlands. Results: The total costs associated with the 2017 outbreak were estimated to be €335,278 (US $356,826); the total costs associated with the 2018 outbreak were estimated at €149,025 (US $158,602). Conclusions: The main drivers of the costs were the opportunity costs due to the reduction in admitted patients, testing costs, and cleaning costs. Although the second outbreak was considerably shorter, the costs per day were similar to those of the first outbreak. Major investments are associated with the VRE control measures, and an outbreak of VRE can lead to considerable costs for a hospital. Aggressively screening and isolating patients who may be involved in an outbreak of VRE may reduce the overall costs and improve the continuity of care within the hospital.